2022
DOI: 10.1142/s2196888822500191
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Traffic Sign Image Generation Applying Generative Adversarial Networks

Abstract: Recently, it was shown that convolutional neural networks (CNNs) with suitably annotated training data and results produce the best traffic sign detection (TSD) and recognition (TSR). The whole system’s efficiency is determined by the data collecting process based on neural networks. As a result, the datasets for traffic signs in most nations throughout the globe are difficult to recognize because of their diversity. To address this problem, we must create a synthetic image to enhance our dataset. We apply dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Subsequently, a collection of labeled images embodying the pests of interest is compiled, with annotations encompassing both the presence and absence of pests, and, where pertinent, the exact species. This dataset is anticipated to be representative, encompassing various life stages and environmental contexts [29,30]. A model with prior training on a comprehensive dataset, such as ResNet 50 or ResNet101 utilizing the ImageNet database, is selected.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Subsequently, a collection of labeled images embodying the pests of interest is compiled, with annotations encompassing both the presence and absence of pests, and, where pertinent, the exact species. This dataset is anticipated to be representative, encompassing various life stages and environmental contexts [29,30]. A model with prior training on a comprehensive dataset, such as ResNet 50 or ResNet101 utilizing the ImageNet database, is selected.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Many hand recognition algorithms in the past depended on skin color segmentation to distinguish and extract hands from the backdrop of images, which was inefficient. In their papers [16,17], Dardas et al suggested a thresholding technique for fragmenting hands in the hue, saturation, and value (HSV) color space after extracting other skin regions, such as the face, from the source image. Girondel and colleagues [18] experimented with a variety of color spaces and discovered that the Cb and Cr channels in the YCbCr color space performed well in the skin detection task.…”
Section: Hand Detection and Recognitionmentioning
confidence: 99%
“…A component of this is making sure that the laws regarding face masks are followed. For instance, the combination of artificial intelligence models and surveillance technologies might be useful in this scenario [14,15].…”
Section: Introductionmentioning
confidence: 99%